PENGARUH PROFITABILITAS, PERTUMBUHAN PENJUALAN, DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL - Ricky Chandra; Jonnardi Sutan (Jurnal Paradigma Akuntansi, 2023)
This research aims to analyze the effect of profitability, sales growth, and company size on capital structure. This research is conducted by using 125 sample data of manufacturing companies in the infrastructure, utility, and transportation sub-sectors listed in Indonesia Stock Exchange in the period 2015-2019. This sampling method is using purposive sampling method and processed using EViews 11 program. The results showed that the profitability variable has a negative and significant effect on the capital structure, the sales growth variable had a positive and significant effect on the capital structure, the firm size variable had a negative and significant effect on the structure capital.